Pressurized Intraperitoneal Aerosol Chemotherapy (PIPAC): A localized drug delivery approach to treat peritoneal carcinomatosis of different origins - Afrin, Sabrina (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2022.